From Cornea to Macula: The Potential Role of Dry Eye–Related Ocular Surface Inflammation in Macular Degeneration - Zhang, Huini (International Journal of Public Health and Medical Research, 2026)
Dry eye is a chronic inflammatory disease of the ocular surface caused by shortened tear film rupture time and high osmotic pressure. Macular degeneration, especially AMD, is one of the main causes of blindness worldwide, traditionally believed to be mainly caused by RPE aging, oxidative damage, and choroidal circulation disorders. In recent years, epidemiological and basic research has also suggested that chronic inflammatory reactions on the ocular surface can participate in the occurrence and development of macular degeneration through common inflammatory pathways, oxidative stress amplification effects, and immune regulation disorders. In summary, this article mainly elaborates on the inflammatory pathway from the cornea to the macular area and the possible ways in which inflammatory mediators extend from the ocular surface to the posterior part of the eye. It also provides new ideas for the involvement of ocular surface inflammation caused by dry eye in the treatment of AMD, hoping to help achieve a multi site integrated diagnosis and treatment model for the eye.